Taming the News Feed on Facebook: Understanding Consumptive News Feed Curation through a Social Cognitive Perspective. Issue 9 (12th November 2020) - Lu, Shuning
Abstract: As algorithms are increasingly integrated into news selection and consumption processes, it is crucial to understand how news users respond to them. Drawing upon social cognitive theory, this study examined the underlying mechanisms of consumptive news feed curation, a type of news consumption behaviour through which news users could determine what shows up in their news feeds. Findings based on a national survey data in the United States showed that the proportion of Facebook users who practiced consumptive news feed curation remained low and the extent of such practices varied according to their socioeconomic and political backgrounds. The study further tested a moderated mediation model and found that Facebook use contributed to consumptive news feed curation through perceived knowledge, depending on levels of perceived user controllability. Theoretical and practical implications are discussed.